2021
DOI: 10.1038/s41598-021-02382-0
|View full text |Cite
|
Sign up to set email alerts
|

Skin irritation and potential antioxidant, anti-collagenase, and anti-elastase activities of edible insect extracts

Abstract: This study aimed to investigate antioxidant, anti-aging, and irritation properties of Thai edible insect extracts, including Bombyx mori, Omphisa fuscidentalis, Euconocephalus sp., Patanga succincta, Acheta domesticus, and Lethocerus indicus. Insects were extracted by 2 different methods, including maceration using ethanol or hexane and digestion using DI water. Then the extracts were determined for protein content using bicinchoninic acid assay and antioxidant activities using 2,2′-azinobis (3-ethylbenzothiaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…These findings confirm the safety of all the A. domesticus extracts for topical applications. The results were in line with our previous study, which reported no skin irritation of A. domesticus extracts in both in vitro HET-CAM and in vivo human patch tests in volunteers [ 21 ]. In addition, no allergens have been reported within crickets, and specific food-related allergies resulting from A. domesticus consumption have not been documented in Europe or regions where cricket consumption is prevalent [ 69 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These findings confirm the safety of all the A. domesticus extracts for topical applications. The results were in line with our previous study, which reported no skin irritation of A. domesticus extracts in both in vitro HET-CAM and in vivo human patch tests in volunteers [ 21 ]. In addition, no allergens have been reported within crickets, and specific food-related allergies resulting from A. domesticus consumption have not been documented in Europe or regions where cricket consumption is prevalent [ 69 ].…”
Section: Resultssupporting
confidence: 92%
“…Although A. domesticus is currently considered edible and is farmed for consumption as food, previous data regarding its biologically active compounds, which highlight it as a rich source of vitamins, fatty acids, and essential amino acids, make it likely to have the potential to be beneficial for topical applications as skin care. Furthermore, our previous study found that A. domesticus aqueous extract demonstrated the most potent biological activities, such as the inhibition of oxidation, matrix metalloproteinase (MMP), and elastase among several insect species [ 21 ]. Additionally, Di Mattia et al (2019) also reported the highest antioxidant activity of the water-soluble extract from A. domesticus compared to other insect species [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…CE was produced through thermal solvent extraction, following the methodology outlined in our earlier study [ 40 ]. Briefly, finely ground A. domesticus powder was extracted with deionized (DI) water for 3 h at 45 °C using a water bath (Memmert, Schwabach, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…However, there is currently no study directly employing A. domesticus to produce PH for anti-skin aging properties. Our previous study revealed that aqueous extracts from A. domesticus demonstrated robust activities against enzymes linked to skin aging and oxidative stress and proposed that the proteins could potentially be responsible for these observed activities [ 40 ]. Consequently, the utilization of enzymatic hydrolysis may further enhance the effectiveness against skin aging and the safety of A. domesticus protein.…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol, a phytochemical, has been identified as the main natural antioxidant in some plants [58]. Researchers have found that aqueous extracts and aqueous ethanol have better antioxidant activity [58,60]. Conversely, other aqueous extracts may contain interesting substances, including fatty acids, particularly unsaturated fatty acids (USFAs), such as αlinolenic acid (ALA), which show β-hexosaminidase-inhibitory activity based on aqueous hexane extracts of Oxya yezoensis [61] and exhibit dominant inhibitory activity against lipid peroxidation in Omphisa fuscidentalis, Euconocephalus sp., Patanga succincta, A. domesticus, and Lethocerus indicus [60].…”
Section: Biological Activitiesmentioning
confidence: 99%